Lupus anticoagulant is the main predictor of adverse pregnancy outcomes in aPL-positive patients: validation of PROMISSE study results. (12th January 2016) - Yelnik, Cecile M; Laskin, Carl A; Porter, T Flint; Branch, D Ware; Buyon, Jill P; Guerra, Marta M; Lockshin, Michael D; Petri, Michelle; Merrill, Joan T; Sammaritano, Lisa R; Kim, Mimi Y; Salmon, Jane E
Abstract : Objective: We previously reported that lupus anticoagulant (LAC) is the main predictor of poor pregnancy outcome in antiphospholipid antibody (aPL)-positive patients. We sought to confirm this finding in an independent group of patients who were subsequently recruited into the PROMISSE study. Methods: The PROMISSE study is a multicentre, prospective, observational study of pregnancy outcomes in women with aPL and/or systemic lupus erythematosus (SLE) that enrolled patients from 2003 to 2015. All consecutive, aPL-positive patients from the PROMISSE study who completed their pregnancy between April 2011 and January 2015 (after the previous PROMISSE report) are included in the current report. Patients were followed monthly until delivery, and aPL was tested at first, second and third trimesters of pregnancy and at 12 weeks post partum. Adverse pregnancy outcomes (APOs) were defined as fetal death after 12 weeks of gestation, neonatal death, delivery prior to 36 weeks of gestation due to pre-eclampsia or placental insufficiency or small-for-gestational age (birth weight <5th percentile). Results: Forty-four aPL-positive patients are included in this paper. Thirteen patients had APOs, which occurred in 80% of cases during the second trimester of pregnancy. LAC was present in 69% of patients with APOs compared with 27% of patients without APOs (p=0.01). No association was found between anticardiolipin antibodies (aCL) or anti-β2 glycoprotein I antibodies (aβ2GPI) IgG or IgM positivity and APOs. Definite antiphospholipid syndrome (history of thrombosis and/or pregnancy morbidity and aPL) was found in 92% of patients with any APOs compared with 45% of patients without APOs (p=0.004). Conversely, the frequency of SLE was not statistically different between those with and without APOs (30% vs 39%). Conclusions: Our findings, in an independent group of aPL-positive patients from the PROMISSE study, confirm that LAC, but not aCL and aβ2GPI, is predictive of poor pregnancy outcomes after 12 weeks of pregnancy. Trial registration number: NCT00198068.